A Novel Truncated Liver Enriched Antimicrobial Peptide-2 Palmitoylated at its N-Terminal Antagonizes Effects of Ghrelin - Holá, Lucie; Železná, Blanka; Karnošová, Alena; Kuneš, Jaroslav; Fehrentz, Jean-Alain; Denoyelle, Séverine; Cantel, Sonia; Blechová, Miroslava; Sýkora, David; Myšková, Aneta; Maletínská, Lenka (The Journal of pharmacology and experimental therapeutics, 2022)
Ghrelin is secreted in the stomach during fasting and targets the growth hormone secretagogue receptor (GHSR1a) in the hypothalamus and brainstem to exert its orexigenic effect. Recently, liver enriched antimicrobial peptide-2 (LEAP2) was identified as an endogenous high-affinity GHSR1a antagonist. LEAP2 is a 40-amino acid peptide with two disulfide bridges and GHRS1a affinity in the N-terminal hydrophobic part. In this study, we tested modified truncated N-terminal peptide LEAP2 (1-14), along with its myristoylated, palmitoylated, and stearoylated analogs, to determine their affinity to and activation of GHSR1a and their anorexigenic effects after acute peripheral administration. The lipidized analogs bound GHSR1a with affinity similar to that of natural LEAP2, and lipidization significantly enhanced the affinity of LEAP2(1-14) to GHSR1a. According to the beta-lactamase reporter gene response, the natural GHSR1a agonist ghrelin activated the receptor with nanomolar EC50 LEAP2(1-14) analogs behaved as inverse agonists of GHSR1a and suppressed internal activity of the receptor with EC50 values in the 10-8 M range. LEAP2(1-14) analogs significantly lowered acute food intake in overnight fasted mice, and palmitoylated LEAP2(1-14) was the most potent. In free-fed mice, all LEAP2(1-14) analogs significantly decreased the orexigenic effect of the stable ghrelin analog [Dpr3]Ghrelin. Moreover, palmitoylated LEAP2(1-14) inhibited the growth hormone (GH) release induced by [Dpr3] Ghrelin and exhibited an increased stability in rat plasma compared with LEAP2(1-14). In conclusion, palmitoylated LEAP2(1-14) had the most pronounced affinity for GHSR1a, had an anorexigenic effect, exhibited stability in rat plasma, and attenuated [Dpr3]Ghrelin-induced GH release. Such properties render palmitoylated LEAP2(1-14) a promising substance for antiobesity treatment. SIGNIFICANCE STATEMENT: The agonist and antagonist of one receptor are rarely found in one organism. For ghrelin receptor (growth hormone secretagogue receptor, GHSR), endogenous agonist ghrelin and endogenous antagonist/inverse agonist liver enriched antimicrobial peptide-2 (LEAP2) co-exist and differently control GHSR signaling. As ghrelin has a unique role in food intake regulation, energy homeostasis, and cytoprotection, lipidized truncated LEAP2 analogs presented in this study could serve not only to reveal the relationship between ghrelin and LEAP2 but also for development of potential anti-obesity agents.
Keywords: Amino Acids; látky proti obezitě; krysa rodu Rattus; Anti-Obesity Agents; aminokyseliny; myši; receptory ghrelinu; Disulfides; Mice; disulfidy; Antimicrobial Peptides; Ghrelin; zvířata; játra; Receptors, Ghrelin; antimikrobiální peptidy; ghrelin; Liver; Rats; Animals; růstový hormon; Growth Hormone